1. Limited time only! Sign up for a free 30min personal tutor trial with Chegg Tutors
    Dismiss Notice
Dismiss Notice
Join Physics Forums Today!
The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

Homework Help: A biconditional statement for arc length of a function

  1. Mar 26, 2013 #1
    1. The problem statement, all variables and given/known data

    Show that [itex]\gamma : [a, b] \rightarrow \Re^{2}[/itex] is a parameterization of [itex]\Gamma[/itex] if and only if the length of the curve from [itex]\gamma(a)[/itex] to [itex]\gamma(s)[/itex] is [itex]s - a[/itex]; i.e.,


    \int ^{s}_{a} \left| \gamma ' (t) \right| dt = s - a.


    2. Relevant equations

    3. The attempt at a solution

    Part 1; show [itex]\left| \gamma ' (s) \right| = 1 \Rightarrow \int ^{s}_{a} \left| \gamma ' (t) \right| dt = s - a.[/itex]

    We have


    \ell = \int ^{b}_{a} \left| \gamma ' (t) \right| dt = \int ^{b}_{a} \left| \gamma ' (s(t)) s'(t) \right| dt = \int ^{b}_{a} \left| \gamma ' (s(t))\right| \left| s'(t) \right| dt = \int ^{\ell}_{0} \left| \gamma ' (s) \right| ds = \int ^{\ell}_{0} 1 ds = s(\ell) - s(0) = s - a.


    My question here is: did I do the change of variables correctly? Specifically in the limits of integration?

    Now how do I prove the converse; i.e., how do I show that [itex]\int ^{s}_{a} \left| \gamma ' (t) \right| dt = s - a \Rightarrow \left| \gamma ' (s) \right| = 1 ?[/itex]

    [itex]\int ^{s}_{a} \left| \gamma ' (t) \right| dt [/itex]
    [itex]= \int ^{s}_{a} \sqrt{x'(t)^{2} + y'(t)^{2} } dt [/itex]
    [itex]= \int ^{s}_{a} \sqrt{ (x'(s(t)) s'(t) )^{2} + (y'(s(t)) s'(t) )^{2} } dt [/itex]
    [itex]= \int ^{s}_{a} \sqrt{ s'(t)^{2} (x'(s)^{2} + y'(s)^{2}) } dt [/itex]
    [itex]= \int ^{s}_{a} s'(t) \sqrt{ (x'(s)^{2} + y'(s)^{2}) } dt [/itex]
    [itex]= \int ^{s}_{t=a} \sqrt{ (x'(s)^{2} + y'(s)^{2}) } ds[/itex]
    [itex]= \int ^{s}_{t=a} \left| \gamma' (s) \right| ds = s - a[/itex]
    [itex]= \frac{d}{ds}(\int ^{s}_{t=a} \left| \gamma' (s) \right| ds)[/itex]
    [itex] = \frac{d}{ds}(s - a)[/itex]
    [itex] = 1 - 0 = 1[/itex]

    so [itex]1 = \left| \gamma' (s) \right| .[/itex]

    or is that garbage?
    Last edited: Mar 26, 2013
  2. jcsd
  3. Mar 26, 2013 #2
    This statement is incorrect. Is it supposed to be "natural parametrization" rather than just "parametrization?
  4. Mar 26, 2013 #3
    I do believe that the statement I am to prove is correct. I have copied it directly out of my text. My instructor says my proof is complete. I'm not sure what you meant.

    And it is natural parametrization.
  5. Mar 26, 2013 #4
    The statement is correct only if it is about natural parametrization. It is not correct for an arbitrary parametrization.
  6. Mar 26, 2013 #5
    Oh my bad. I failed to mention that in my
Share this great discussion with others via Reddit, Google+, Twitter, or Facebook

Have something to add?
Draft saved Draft deleted